Image-based center of mass estimation of the human body via 3D shape and kinematic structure - Kaichi, T.; Mori, S.; Saito, H.; Takahashi, K.; Mikami, D.; Isogawa, M.; Kusachi, Y. (Sports Engineering, 2019)
This paper presents a method to estimate a time-sequential trajectory of the center of mass (CoM) of an athlete from a multi-view set of cameras. Collecting the CoM typically requires large-scale measuring systems or attaching sensors to the athletes. To mitigate such hardware limitations, the present study takes a multi-view video-based approach. The proposed method reconstructs subjects` voxels from a set of multi-view frames and weights each voxel with body part-dependent weights to calculate a CoM. Our results, using real data measured in a studio, showed that the proposed method can estimate CoM within 20 mm concerning center of pressure measures.